(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article examines the issues of ensuring the liquidity of economic entities operating in the Republic of Uzbekistan. In the course of the research, the opinions of economists regarding the liquidity of economic entities were studied, and an analysis of the liquidity of economic entities operating in Uzbekistan was conducted. Based on the results of the analysis, relevant conclusions and proposals were developed.